Peer victimization at school and associated factors in Campeche, Mexico - Héctor Javier Sánchez-Pérez; Edith Zúñiga Vega; Ángel Sinaí Sosa Salazar; Sergio Alvarado Orellana; Natalia Romero-Sandoval; Miguel Martín
Abstract Objectives: to estimate the prevalence ofpeer victimization (VI-P) and to identify factors associated to it. Methods: a cross sectional study based on a state-representativesample; 2555 students from primary and secondary schools of Campeche, in the academic year 2015-2016 participated. They were interviewed face to face. VI-P was analyzed by sex, age and various school-related aspects with prevalence rate and 95% confidence interval. The analysis of interactions among the studied factors was carried out using a hierarchical log-lineal model. With the significant terms,a multiviarite analysis using a logistic model was performed. Based on this model, maximum and minimum predictive values for VI-P were calculated by odds inverse transformation. Results: the global prevalence of VI-P was 60.4% (CI95%= 58.6-62.3). The prevalence of violence physical, psycho-emotional, patrimonial, and sexual, were 28.8, 52.9, 26.5, and 8.7%, respectively. Students in the first year, who were male, had classes scheduled in the evening, attended a public school and resided in a municipality of high/highest margination index, had the highest probability (75.3%) of suffering VI-P. Conclusions: given the high levels of VI-P found, and its possible effects, it is necessary implement truly effective measures to prevent it.